(untitled) (International Journal of Nursing Care, 2020)
Automated external defibrillator is a portable electronic device that delivers an electric shock to the heart muscles through the chest wall in order to resolve a normal heart rate. The AED will analyse the heart’s electrical rhythm and if it detects a rhythm likely to respond to a shock, it will charge itself ready to deliver a shock. Aim: To assess the level of knowledge regarding the use of AED machine among the railway employees in a selected railway station at Kannur districts. Objectives: The objectives of the study are to, • assess the level of knowledge regarding the use of AED among railway employees • find the association between knowledge and selected demographic variables among railway employees. Methodology: The study was conducted to assess the knowledge regarding use of AED among the railway employees in a selected railway station at Kannur district. Non experimental quantitative approach was used for this study. A total of 30 samples were selected using convenient sampling technique. Formal written permission was obtained from the authorities prior to the data collection process. The data was analyzed by using both descriptive and inferential statistics on the basis of the objectives and hypothesis of the study. Result: The study showed that 6.66% of railway employees have good knowledge, 70% of employees have moderate knowledge, 23.33% railway employees have poor knowledge regarding the use of AED and there was no association between knowledge and selected demographic variables except year of experience of the employees.